Lignin-derived carbon nanofibers with the micro-cracking structure for high-performance capacitive deionization. Issue 6 (December 2022) - Li, Chun-Ping; Wu, Ya-Qi; Gao, Li-Xin; Zhang, Da-Quan; An, Zhong-Xun
Abstract: The binder-free electrode materials have excellent practical application value, especially for carbon-based electrodes. As a naturally occurring carbon precursor, lignin can be developed for the electrode material of capacitive deionization with high energy storage and high adsorption performance. In this paper, nanofibers containing mesoporous fracture systems are prepared by depolymerized lignin. The microcracks are uniformly distributed on the carbon nanofiber tube bundles. It can provide a favorable place for ion storage, and the notches structure further improves the ion adsorption performance. This study provides a simple and efficient strategy for the converting lignin into carbon fibers with the micro-cracking structure. It is expected to promote the application of lignin-based carbon nanofibers in capacitive deionization. Highlights: The small molecular snippets lignin is obtained from the Pre-catalytic oxidative degradation. Functionalized nanofibers containing mesoporous fracture systems were prepared by depolymerized lignin. The adsorption capacity of nanofibers is 18.8 mg g −1 with a 90% adsorption capacity retention rate.